Broad‐Spectrum Antifungal Agents: Fluorinated Aryl‐ and Heteroaryl‐Substituted Hydrazones. (16th October 2020) - Thamban Chandrika, Nishad; Dennis, Emily K.; Brubaker, Katelyn R.; Kwiatkowski, Stefan; Watt, David S.; Garneau‐Tsodikova, Sylvie
Abstract: Fluorinated aryl‐ and heteroaryl‐substituted monohydrazones displayed excellent broad‐spectrum activity against various fungal strains, including a panel of clinically relevant Candida auris strains relative to a control antifungal agent, voriconazole (VRC). These monohydrazones displayed less hemolysis of murine red blood cells than that of VRC at the same concentrations, possessed fungicidal activity in a time‐kill study, and exhibited no mammalian cell cytotoxicity. In addition, these monohydrazones prevented the formation of biofilms that otherwise block antibiotic effectiveness and did not trigger the development of resistance when exposed to C. auris AR Bank # 0390 over 15 passages. Abstract : Antifungal drug development : The synthesis and biological activity of fluorinated aryl‐ and heteroaryl‐substituted monohydrazones are presented. In most cases, the antifungal activity of these new compounds exceeded those of reference drugs against various fungal strains tested. All the lead compounds exhibited better safety profiles and there was low incident of resistance development. Thus, these fluorinated aryl‐ and heteroaryl‐substituted monohydrazones could lead to the development of novel antifungal agents.